Assessment of utilization of antenatal care services by mothers attending immunization sessions at a primary health centre in Mysore district, Karnataka, India - M. R., Narayana Murthy; Siddalingappa, Hugara; Mishra, Banani (International Journal Of Community Medicine And Public Health, 2016)
Background: Health status of any community depends on the care provided to its vulnerable population like women and children. Good care during pregnancy assures an uneventful childbirth and healthy mother and child. Hence this study was conducted to assess utilization of antenatal care (ANC) services by mothers attending immunization clinics in a primary health centre (PHC) and subcentres. Methods:In this facility based cross sectional study, 200 mothers who delivered between July 2012 to June 2013 were interviewed using a questionnaire. Details regarding antenatal checkups were noted down from Thayi card. Results: Full ANC services were utilized by 93% women. All mothers had registered pregnancy and most within 1st trimester. 61% were staying in village more than 10 km away from a PHC. 42.5% of mothers had married before 18 years and 54.5% had their first pregnancy between 15 to 20 years. Conclusions: Awareness and utilization of ANC services was high in the study area. Child marriage and teen age pregnancies were considerably high.